Effect of Feeding Different Levels of Ajwain (Trachyspermum ammi L.) Powder on Growth Performance and Carcass Characteristics in Japanese quails - Deepthi, M.; Kumar, D. Srinivas; Rao, E. Raghava; Rao, S. Jagadeeswara (Indian Journal of Animal Nutrition, 2020)
An experiment was carried out to study the effect of inclusion of ajwain powder at varying levels on growth performance, carcass characteristics and nutrient utilization in Japanese quails. One hundred and fifty day-old quail chicks were randomly allotted to five dietary treatment groups with 3 replicates of 10 birds for 5 weeks. Ajwain was ground and included at 0% (T1; Control), 0.25 (T2), 0.50 (T3), 0.75 (T4) and 1.0 (T5) percent levels in iso-caloric and iso-nitrogenous broiler quail diets to meet the nutrient requirements as per NRC, 1994. Body weight gain and feed intake were recorded while feed efficiency was calculated. Results indicated that inclusion of ajwain powder up to 1.0% level in the diet of Japanese quail had no effect (P>0.05) on body weight gains, feed intake and on feed consumed / kg gain. Similarly, inclusion of ajwain powder up to 1.0% level in the diet had no effect (P>0.05) on carcass characteristics in quails. The feed cost / kg gain decreased by 1.01 in T2 while it was Â increased by 4.11 in T3, 6.84 in T4 and 9.55 in T5 groups of quails fed diets containing ajwain powder up to 1.0% level as compared to the control.